PENGENALAN TEKNOLOGI AUGMENTED REALITY DAN VIRTUAL REALITY SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BAGI SISWA - Desfa Anisa; Widya Putri; Eka Fitri Amir (LPPM Universitas Awal Bros, 2026)
The advancement of digital technology in the Industrial Revolution 5.0 era has opened up significant opportunities for education, particularly through the application of Augmented Reality (AR) and Virtual Reality (VR) technologies. These technologies can also be utilized as learning media. However, at the high school level, the use of AR and VR is still very limited, and many teachers and students do not yet understand how to use them. The learning process is still dominated by textbooks, making it less engaging for students. This community service program aims to introduce and implement AR and VR as interactive learning media in the school environment. The activity took place at SMAN 23 Batam and was attended by 35 participants. The implementation method for this activity included socialization and AR and VR simulations. The activity was evaluated using a questionnaire to measure the level of understanding and perception of participants regarding the implementation of the activity. The evaluation results showed that 88.57% of participants strongly agreed that this activity increased their insight into AR and VR technology, 74.29% of participants strongly agreed that they understood the differences between AR and VR, and 82.86% of participants strongly agreed that the activity provided benefits to them. These results indicate that the AR/VR introductory activity successfully increased students' understanding, interest, and motivation towards using digital technology in learning. Therefore, this activity can be an effort to support increased technological literacy and the implementation of technology-based learning in the school environment.